Calquemath Berbasis Kodular: Studi Etnomatematika Arsitektur Masjid Kyai Syakir Wotgalih Indramayu - Adibba, Aulya; Mellawaty, Mellawaty (JURNAL MathEdu (Mathematic Education Journal), 2025)
contextual relevance. This study aims to develop Calquemath, an Android-based calculus learning application that integrates architectural elements of the Kyai Syakir Mosque in Wotgalih, Indramayu, as an ethnomathematical context. The media development followed the 4D model, limited to the develop stage. The define stage involved needs analysis, exploration of local cultural potential, and literature review. The design stage included initial media design using Kodular, incorporating content on curved solid geometry (hemisphere, cone, and cylinder) connected to integral concepts. The develop stage consisted of prototype creation and expert validation by two mathematics education lecturers and one mathematics teacher. The validation instrument covered aspects of content feasibility, visual appearance, interactivity, and integration of ethnomathematical context. Validation results indicate that Calquemath falls into the “highly feasible” category as a learning medium, based on expert assessments of visual quality, readability, interactivity, and ease of navigation. Future research is recommended to proceed to the disseminate stage to measure the media’s effectiveness in enhancing students’ understanding of calculus concepts.